Targeting Notch1 for Neuroinflammatory Immunotherapy: Insights from a Neuronal Apoptosis Model - Jiang, Shuyuan; Wei, Xie (Trends in Immunotherapy, 2025)
The Notch1 signaling pathway is pivotal in neuroimmunomodulation and inflammation, and it significantly contributes to the development and pathogenesis of the nervous system. Consequently, targeting Notch signaling may offer a promising therapeutic approach for neurological disorders. In this investigation, we elucidated the crucial role of Notch1 signaling in neuronal apoptosis, immune regulation, and inflammatory signaling by knocking down the Notch1 gene in mouse hippocampal HT22 cells. Suppression of Notch1 resulted in a marked reduction in the expression of its downstream effector molecule Hes1, accompanied by a significant rise in apoptosis, increased levels of apoptosis-related proteins, and diminished cell viability. RNA sequencing analyses further revealed that differential expression was closely linked to apoptosis, immune-regulatory pathways, and inflammatory signaling. Apoptosis serves as a critical mechanism for eliminating abnormal cells and can impact immune response balance by modulating immune cell activation and function. Notch1 signaling can indirectly affect the neuroimmune microenvironment by regulating neuronal apoptosis. Thus, targeting the Notch1 signaling pathway not only safeguards neuronal function by inhibiting apoptosis but also modulates immune cell activation and inflammatory responses, offering a novel strategy for the immunotherapy of neurodegenerative and cerebrovascular diseases. Comprehending this mechanism provides a crucial foundation for exploring Notch1 immunotherapy for these conditions. By precisely modulating Notch1 signaling, it is anticipated that future therapies can achieve the dual benefits of neuroprotection and immunomodulation, paving the way for innovative treatments for related diseases.